2020
DOI: 10.1097/inf.0000000000002674
|View full text |Cite
|
Sign up to set email alerts
|

Screening-based and Risk-based Strategy for the Prevention of Early-onset Group B Streptococcus/Non-group B Streptococcus Sepsis in the Neonate: A Systematic Review and Meta-analysis

Abstract: Background: Screening-based and risk-based strategies are the 2 strategies for preventing group B streptococcus (GBS) diseases in neonates. We aimed to compare the effects of these 2 strategies in reducing the incidence of early-onset GBS sepsis (GBS-EOS) and their effects on the incidence of non-GBS sepsis. Methods: PubMed, Embase, Web of Science and The Cochrane Central Register of Controlled Trials were searched for the period from January 1, 1996, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The overall mortality rate in our cohort was compatible with recent studies [ 3 , 4 , 5 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] and a reduction in mortality between 2012 and 2020 was observed in our cohort. As reported in recent studies, multiple factors may account for the reduced mortality rate, including widespread implementation of antibiotics in at-risk mothers and babies and advances in managing acutely ill neonates [ 33 , 34 ]. Based on our data, neonatal GBS EOD had a significantly higher rate of complicated sepsis and a higher rate of final mortality than GBS LOD.…”
Section: Discussionmentioning
confidence: 99%
“…The overall mortality rate in our cohort was compatible with recent studies [ 3 , 4 , 5 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] and a reduction in mortality between 2012 and 2020 was observed in our cohort. As reported in recent studies, multiple factors may account for the reduced mortality rate, including widespread implementation of antibiotics in at-risk mothers and babies and advances in managing acutely ill neonates [ 33 , 34 ]. Based on our data, neonatal GBS EOD had a significantly higher rate of complicated sepsis and a higher rate of final mortality than GBS LOD.…”
Section: Discussionmentioning
confidence: 99%
“…Prevention IAP for at-risk women has become the standard of care in many countries over the past two decades and is an effective way to prevent EOS (102)(103)(104). A meta-analysis revealed that compared with a risk-based strategy, screening-based prophylaxis was associated with a reduced risk of GBS-EOS (105). The Society of Obstetricians and Gynecologists of Canada (SOGC), in 2018, reaffirmed the recommendation of offering all women screening for colonization with GBS at 35-37 weeks of gestation, by performing culture tests with one swab from the vagina and one from the rectum (106).…”
Section: Duration Of Therapy For Positive Blood Culturementioning
confidence: 99%
“…Similar numbers of women received antibiotics with either approach. Table 2 lists findings from these reviews 171819. No difference was seen in early onset GBS infection rates between risk factor directed protocols for giving IAP compared with no consistent IAP protocol 17.…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 99%
“…This yielded 60 results, including three systematic reviews of screening for GBS from 2019 to 2020131420 and one diagnostic test accuracy review of molecular testing methods, which was included in this article 12. The 2016 review of the National Screening Committee criteria and outputs from the British Perinatal Surveillance Unit provided further information 1218…”
Section: Is Ongoing Research Likely To Provide Relevant Evidence?mentioning
confidence: 99%